If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + 6) + 6 = (x + 2) + 3 Reorder the terms: -4(6 + x) + 6 = (x + 2) + 3 (6 * -4 + x * -4) + 6 = (x + 2) + 3 (-24 + -4x) + 6 = (x + 2) + 3 Reorder the terms: -24 + 6 + -4x = (x + 2) + 3 Combine like terms: -24 + 6 = -18 -18 + -4x = (x + 2) + 3 Reorder the terms: -18 + -4x = (2 + x) + 3 Remove parenthesis around (2 + x) -18 + -4x = 2 + x + 3 Reorder the terms: -18 + -4x = 2 + 3 + x Combine like terms: 2 + 3 = 5 -18 + -4x = 5 + x Solving -18 + -4x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -18 + -4x + -1x = 5 + x + -1x Combine like terms: -4x + -1x = -5x -18 + -5x = 5 + x + -1x Combine like terms: x + -1x = 0 -18 + -5x = 5 + 0 -18 + -5x = 5 Add '18' to each side of the equation. -18 + 18 + -5x = 5 + 18 Combine like terms: -18 + 18 = 0 0 + -5x = 5 + 18 -5x = 5 + 18 Combine like terms: 5 + 18 = 23 -5x = 23 Divide each side by '-5'. x = -4.6 Simplifying x = -4.6
| -9x+5y=-1 | | 1=-y-6/y-1+y-5/y+1 | | 13x-8+3x-4=12x-4+3x | | 5(x-7)+9=2(x-4) | | 2log(x)-log(x+2)=2 | | 90=x+(x-40) | | 0.5x-0.7(5-x)=4.3 | | 2x+6=3(x-5) | | x/4-4/x | | 5/4x-1/4x+14=9/10 | | U*6-4=7 | | 9/4-9/x/x/4-4/x | | 3x-7x-7=-4x+2-7 | | 2logx-log(x+2)=2 | | 6x=(7x+20) | | 9/4-9/x | | G-2/3=7/8 | | 4-1n=30 | | X*.8=40 | | 2x-8(2-x)=3 | | 3x-30y=-27 | | -1/2v+4+2=-7/v+2 | | 3(x+15)=2(2x+10) | | 6/v+5-2/v+5=4 | | 0.8y=6 | | 16(y-9)+2y=8y-3(20) | | 5/7x1/4x+10=9/14 | | 4n-1=30 | | 4(x+6)=44 | | 7*(4(1/3))+2 | | X/-5=-11.3 | | 4(z-3)+5z-1= |